Impact of Pre-Menstrual Syndrome on Academic Performance of Undergraduates Medical Students - Maroofa Habib, Ifrah Gul, Aqsa Iqbal, Shagufta Sikandar, Tayyaba Majeed, Mariam Malik, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study aims to investigate the effect of PMS on the academic performance of undergraduate medical students. Materials & Methods: The present study was cross sectional and analytical involving 49 undergraduate medical students. A structured proforma was used to gather information about the demographic characteristics, menstrual history, and body mass index (BMI), as well as information about the severity of premenstrual symptoms. The severity of premenstrual syndrome was determined by a premenstrual symptom score and the participants divided into lower and higher PMS severity groups. Students' academic performance was divided into good and poor performance groups. The data were analyzed statistically by using the methods similar to the Statistical Package for the Social Sciences (SPSS). Data were presented as mean ± standard deviation for continuous variables and frequencies and percentages for categorical variables. Where appropriate, the chi-square test was used and independent sample t-test was used, p<0.05 being statistically significant. Results: The mean age of participants was 22.65 ± 1.52 years, while the mean BMI was 23.66 ± 2.03 kg/m². The mean age at menarche was 12.08 ± 1.09 years, and the overall mean PMS score was 26.22 ± 3.99. Of the participants 26 (53.1%) were classified into the lower group of severity of PMS and 23 (46.9%) were classified into the higher group of severity of PMS. The good academic performance was noted among 31 (63.3%) students while the poor academic performance was noted among 18 (36.7%) students. There was a statistically significant relationship between the level of severity of PMS and academic performance (p<0.001). Academically poor students scored significantly higher on the PMS than did good academic students (30.17 ± 2.76 vs 23.94 ± 2.31; p<0.001). Conclusion: Undergraduate medical students are highly affected by PMS and suffer in their academic performance. The higher the level of severity of the PMS, the poorer the academic outcomes. Recognizing the importance of early identification, awareness initiatives, and suitable care and management practices, can lead to better learning outcomes and general health for students who are impacted. Keywords: PMS; academic performance; medical students; menstrual health; and severity of PMS.